Makna Simbolik Pantun Banjar Samarinda dalam Teater Tradisional Sandima (Studi Kasus Pergelaran â€œPPKMâ€ Taman Budaya Kalimantan Timur) - Al Fayed, Muhammad; Simatupang, G. R. Lono Lastoro (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This study aims to determine the origin of the banjar rhyme tradition, as well as to reveal the symbolic meaning of the Banjar Samarinda rhyme in the Sandima performance. This study uses a qualitative descriptive type of research that tries to explain, tell, describe, analyze and so on about the beginning of the Banjar pantun tradition in Samarinda, East Kalimantan in the Sandima traditional theater performance. The results of this study also reveal and find out the true meaning of the rhyme in Sandima's traditional theater performance entitled